2021
DOI: 10.1186/s12866-021-02398-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence factors of Salmonella isolated from human stools and street food in urban areas of Burkina Faso

Abstract: Background This study was undertaken to identify and functionally characterize virulence genes from Salmonella isolates in street food and stool cultures. From February 2017 to May 2018, clinical and food Salmonella strains were isolated in three regions in Burkina Faso. Salmonella was serotyped according to the White-Kauffmann-Le Minor method, and polymerase chain reaction (PCR) was used to detec invA, spvR, spvC, fimA and stn virulence genes commonly associated with salmonellosis in Sub-Sahar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 53 publications
(58 reference statements)
1
16
1
Order By: Relevance
“…In developing countries such as Burkina Faso, numerous studies have previously reported the presence of Salmonella spp. in RTE foods [30][31][32]. Te potential hygiene breakdowns at various stages of the food processing and distribution chain due to the lack of food safety regulations and food handler educations are responsible for food contamination in developing countries [33].…”
Section: Presumptive Salmonella Isolates and Molecularmentioning
confidence: 99%
“…In developing countries such as Burkina Faso, numerous studies have previously reported the presence of Salmonella spp. in RTE foods [30][31][32]. Te potential hygiene breakdowns at various stages of the food processing and distribution chain due to the lack of food safety regulations and food handler educations are responsible for food contamination in developing countries [33].…”
Section: Presumptive Salmonella Isolates and Molecularmentioning
confidence: 99%
“…Six pairs of antibiotic-resistant gene and eleven pairs of SPI1-6 virulence gene amplification primers were designed based on the gene sequences in GenBank and the literature (5,(11)(12)(13)(14)(15)(16)(17)(18). All PCR products were sequenced using primer walking, starting with 3CS and 5CS primers (Table 1).…”
Section: Determination Of Antibiotic Resistance Genes and Spi1-6 Genesmentioning
confidence: 99%
“…The main sources of human salmonellosis are contaminated food products of animal origin such as dairy products and direct contact with infected animals [ 4 , 5 ]. Salmonella infection on cattle farms continues to be a major problem, causing economic losses and increasing the risk of transmission to humans.…”
Section: Introductionmentioning
confidence: 99%